Tectono‐sedimentary evolution of the northern Iranian Plateau: insights from middle–late Miocene foreland‐basin deposits. (17th February 2016) - Ballato, Paolo; Cifelli, Francesca; Heidarzadeh, Ghasem; Ghassemi, Mohammad R.; Wickert, Andrew D.; Hassanzadeh, Jamshid; Dupont‐Nivet, Guillaume; Balling, Philipp; Sudo, Masafumi; Zeilinger, Gerold; Schmitt, Axel K.; Mattei, Massimo; et al.
Abstract: Sedimentary basins in the interior of orogenic plateaus can provide unique insights into the early history of plateau evolution and related geodynamic processes. The northern sectors of the Iranian Plateau of the Arabia–Eurasia collision zone offer the unique possibility to study middle–late Miocene terrestrial clastic and volcaniclastic sediments that allow assessing the nascent stages of collisional plateau formation. In particular, these sedimentary archives allow investigating several debated and poorly understood issues associated with the long‐term evolution of the Iranian Plateau, including the regional spatio‐temporal characteristics of sedimentation and deformation and the mechanisms of plateau growth. We document that middle–late Miocene crustal shortening and thickening processes led to the growth of a basement‐cored range (Takab Range Complex) in the interior of the plateau. This triggered the development of a foreland‐basin (Great Pari Basin) to the east between 16.5 and 10.7 Ma. By 10.7 Ma, a fast progradation of conglomerates over the foreland strata occurred, most likely during a decrease in flexural subsidence triggered by rock uplift along an intraforeland basement‐cored range (Mahneshan Range Complex). This was in turn followed by the final incorporation of the foreland deposits into the orogenic system and ensuing compartmentalization of the formerly contiguous foreland into several intermontane basins. Overall, our data suggest that shortening and thickening processes led to the outward and vertical growth of the northern sectors of the Iranian Plateau starting from the middle Miocene. This implies that mantle‐flow processes may have had a limited contribution toward building the Iranian Plateau in NW Iran.